Burhs, burghal territories and hundreds in the English central Midlands in the early tenth century. Part 1. (2nd January 2023) - Haslam, Jeremy
ABSTRACT: The strategic context of new burhs created by the West Saxon King Edward the Elder in the east and central Midlands, in part documented in the Anglo-Saxon Chronicle, is examined to determine the ways in which the foundation of these burhs as new fortified settlements was associated with the formation of new burghal territories to maintain their strategic functionality. These burghal territories typically comprised one or more units of around 300+ hides, here termed 'proto-hundreds'. All of these are argued as constituting elements of a major reorganisation of the administrative landscape as part of the essential infrastructure of burghal formation. These new cadastral redevelopments demonstrate the organisational precocity of the West Saxon state at this period. These 'proto-hundreds' were subsequently divided into smaller units of around 100 hides in a new phase of reorganisation which was arguably concurrent with the creation of the shires, formed by amalgamation of the earlier burghal territories, in probably the third quarter of the tenth century. The first part of this paper examines the shires of Buckinghamshire and what is now western Northamptonshire; the second part extends this analysis to Bedfordshire, Hertfordshire, Middlesex, Huntingdonshire and Cambridgeshire.